Transformación de Ecuación General A Canónica
Transformación de Ecuación General A Canónica
Transformación de Ecuación General A Canónica
( ( )) ( ( )) ()()
2 2 2 2
2 2 2 2 2 4
x +2 x + + y +4 y+ =11+ +
2 2 2 2
( x 2 +2 x +1 ) + ( y 2+ 4 y + 4 ) =11+1+ 4
( x +1 )2+ ( y+ 2 )2=16
Gráfica
Elementos
C ( h , k ) ⇒C (−1 ,−2 )
r 2=16 ⇒ r=4
( ( )) ( ( )) () ()
2 2 2 2
2 4 2 2 4 2
9 x −4 x+ + 25 y +2 y + =164+ 9 +25
2 2 2 2
{
2 2
( x−h ) ( y + k ) a=5
+ =1 , por lo tanto:
a2 b2 b=3
c=4
h=1 y k =5
2
a =25 → a=5 C ( h , k ) → C ( 2 ,−1 )
2
b =9 → b=3 V 1 ( h+a , k ) → V 1 ( 2+5 ,−1 ) → V 1 (−7 ,−1 )
2 2 2
a =b +c
2 2 2 V 2 ( h−a , k ) → V 2 ( 2−5 ,−1 ) → V 2 (−3 ,−1 )
c =a −b
c= √ a 2−b2 → c=√ 52−32 F 1 ( h+ c , k ) → F 1 ( 2+ 4 ,−1 ) → F 1 ( 6 ,−1 )
c= √ 16 → c=4 F 2 ( h−c , k ) → F 2 ( 2−4 ,−1 ) → F 2 (−2 ,−1 )
Gráfica
B1 ( h ,k + b ) → B1 ( 2 ,−1+3 ) → B1 ( 2 ,2 )
B2 ( h ,k −b ) → B2 ( 2 ,−1−3 ) → B1 ( 2 ,−4 )
Eje mayor:2 a=2 ( 5 )=10
Eje menor:2 b=2 ( 3 )=6
Eje focal. 2 c=2 ( 4 )=8
2
2 b2 2 ( 3)
LR= → LR= → LR=3 , 6
a 5
c 4
e= →e=
a 5
( ( )) ()
2 2
2 2 2
x −2 x+ =16 y−81+
2 2
( ( )) ( ( )) ()()
2 2 2 2
02 2 0 0 0
9 x +0 x + −4 y +0 y + =36+ +
2 2 2 2
{
a2 b2 a=2
2
a =4 → a=2 b=3
2
c=√ 13
b =9 → b=3
2 2 2
C (0 , 0 )
c =a + b
V 1 (+ a , 0 ) →V 1 ( 2 ,0 )
c= √ a 2+ b2 → c= √ 4+ 9
V 2 (−a , 0 ) →V 2 (−2 , 0 )
c= √ 13
F 1 ( +c , 0 ) → F 1 ( √ 13 , 0 )
Gráfica F 2 (−c , 0 ) → F 2 ( √ 13 , 0 )
B1 ( 0 ,+ b ) → B1 ( 0 ,3 )
B2 ( 0 ,−b ) → B 2 ( 0 ,−3 )
2
2 b2 2 ( 3)
LR= → LR= → LR=9
a 2
c
e= →e=
√ 13
a 5
Asíntotas
b 3
l 1 : y= x → y= x → 3 x−2 y =0
a 2
−b −3
l 2 : y= x → y= x → 3 x +2 y=0
a 2
Eje transverso:2 a=2 ( 2 )=4
Eje conjugado:2 b=2 ( 3 )=6
Eje focal. 2 c=2 ( √ 13 )=2 √ 13